Exploring Christological Controversies in the Gondarine Period: The Significance of Amba Č̣ara Council and the Role of Täwahədo and Qəbat Monastic Clergies, 1622-1854 - Admasu, Bitwoded; Mekonnen, Teferi; Sahile, Sisay (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2023)
This paper attempted to explores the nature of religious controversy among Täwahədo, Şäggočč, and Qəbatočč. It also tried to figure out its far reaching consequences on the state politics in the mid nineteenth century. Although religious controversy within the Ethiopian Orthodox Church was appeared following the advent of Catholic missionaries in the early sixteenth century, the issue was hot agenda during the first fourteen years of the episcopacy of Abunä Sälama III who was said to have deeply affected by theological disputes. The researcher used qualitative research methodology and consulted both primary and secondary sources. The findings of the research revealed that the empowerment of the metropolitan’s authority over the Ethiopian Orthodox Täwahədo Church by Emperor Tewodros II at the council of Amba Č̣ara led to the foundation stone for the termination of the factions which has great implication for the unity of the state. This council became a vital launching spring board for the Boru Meda synod that was held in 1878. Since the defeat of the various war lords silenced the religious factions that considerably enriched Sälamas space for action. Therefore, the pattern of relations which was established between Abunä Sälama III and Tewodros II at the council of Amba Č̣ara proved a guideline principle for succeeding rulers of Ethiopia.